MicroRNA regulation of viral immunity, latency, and carcinogenesis of selected tumor viruses and HIV. (10th August 2015) - Wang, Ling; Li, Guangyu; Yao, Zhi Q.; Moorman, Jonathan P.; Ning, Shunbin
Summary: MicroRNAs (miRNAs) function as key regulators in immune responses and cancer development. In the contexts of infection with oncogenic viruses, miRNAs are engaged in viral persistence, latency establishment and maintenance, and oncogenesis. In this review, we summarize the potential roles and mechanisms of viral and cellular miRNAs in the host–pathogen interactions during infection with selected tumor viruses and HIV, which include (i) repressing viral replication and facilitating latency establishment by targeting viral transcripts, (ii) evading innate and adaptive immune responses via toll‐like receptors, RIG‐I‐like receptors, T‐cell receptor, and B‐cell receptor pathways by targeting signaling molecules such as TRAF6, IRAK1, IKKε, and MyD88, as well as downstream targets including regulatory cytokines such as tumor necrosis factor α, interferon γ, interleukin 10, and transforming growth factor β, (iii) antagonizing intrinsic and extrinsic apoptosis pathways by targeting pro‐apoptotic or anti‐apoptotic gene transcripts such as the Bcl‐2 family and caspase‐3, (iv) modulating cell proliferation and survival through regulation of the Wnt, PI3K/Akt, Erk/MAPK, and Jak/STAT signaling pathways, as well as the signaling pathways triggered by viral oncoproteins such as Epstein–Barr Virus LMP1, by targeting Wnt‐inhibiting factor 1, SHIP, pTEN, and SOCSs, and (v) regulating cell cycle progression by targeting cell cycle inhibitors such as p21/WAF1 and p27/KIP1. Further elucidation of the interaction between miRNAs and these key biological events will facilitate our understanding of the pathogenesis of viral latency and oncogenesis and may lead to the identification of miRNAs as novel targets for developing new therapeutic or preventive interventions. Copyright © 2015 John Wiley & Sons, Ltd.